Preliminary antibacterial evaluation of Eucheuma cottonii gel hand sanitizer - Sukmawati; Dewi , Nurul Kusuma; Cahyani, Nur Tri; Badaruddin, M Iksan (Edubiotik : Jurnal Pendidikan, Biologi dan Terapan, 2026)
Marine-derived bioactive compounds have attracted increasing attention as natural antimicrobial agents for environmentally friendly hygiene products. Eucheuma cottonii, a red seaweed widely cultivated in Indonesia, contains phenolic compounds, flavonoids, and sulfated polysaccharides with potential antibacterial activity. This study examined the antibacterial activity of a hand sanitizer formulated with E. cottonii gel against selected pathogenic bacteria. Antibacterial activity was assessed using the disc diffusion method on Nutrient Agar against Escherichia coli FNCC 0091, Staphylococcus aureus FNCC 0047, and Salmonella typhimurium FNCC 0050. Treatments included E. cottonii gel hand sanitizer, a commercial hand sanitizer as a positive control, and distilled water as a negative control, each tested in triplicate. The E. cottonii gel hand sanitizer produced inhibition zones of 5 mm against E. coli, 10 mm against S. aureus, and 9 mm against S. typhimurium, whereas the commercial product produced inhibition zones of 2, 1, and 1 mm, respectively. These findings indicate that E. cottonii gel has promising preliminary antibacterial potential as a natural ingredient for hand sanitizer formulations, although further studies on formulation optimization, stability, and safety are urgently required.